Finding the lost one - Leer, Samantha van (New York : Pixel + Ink, 2025)
"Thirteen-year-old Ava helps run her family's refuge for extraterrestrials, but a sudden attack on the zoo leads to her discovering a government conspiracy that upends everything"--
Ages 10 to 14.
Grades 7-9.
Keywords: Zoos -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Grief -- Juvenile fiction; Conspiracies -- Juvenile fiction; Science fiction; Novels